Micro-CT-Based Quantification of Extracted Thrombus Burden Characteristics and Association With Angiographic Outcomes in Patients With ST-Elevation Myocardial Infarction: The QUEST-STEMI Study - Karagiannidis, Efstratios; Papazoglou, Andreas S; Sofidis, Georgios; Chatzinikolaou, Evangelia; Keklikoglou, Kleoniki; Panteris, Eleftherios; Kartas, Anastasios; Stalikas, Nikolaos; Zegkos, Thomas; Girtovitis, Fotios; Moysidis, Dimitrios V.; Stefanopoulos, Leandros; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Angiographic detection of thrombus in STEMI is associated with adverse outcomes. However, routine thrombus aspiration failed to demonstrate the anticipated benefit. Hence, management of high coronary thrombus burden remains challenging. We sought to assess for the first time extracted thrombotic material characteristics utilizing micro-Computed Tomography. Methods 113 STEMI patients undergoing thrombus aspiration were enrolled. Micro-CT was undertaken to quantify retrieved thrombus volume, surface and density. Correlation of these indices with angiographic and electrocardiographic outcomes was performed. Results Mean aspirated thrombus volume, surface and density (±standard deviation) were: 15.71 ± 20.10 mm3, 302.89 ± 692.54 mm2 and 3139.04 ± 901.88 Hounsfield Units, respectively. Aspirated volume and surface were significantly higher (p<0.001) in patients with higher angiographic thrombus burden. After multivariable analysis, independent predictors for thrombus volume were: reference vessel diameter (RVD) (p=0.011), right coronary artery (RCA) (p=0.039) and smoking (p=0.027), whereas RVD (p=0.018) and RCA (p=0.019) were predictive for thrombus surface. Thrombus volume and surface were independently associated with distal embolization (p=0.007 and p=0.028, respectively), no-reflow phenomenon (p=0.002 and p=0.006, respectively) and angiographically evident residual thrombus (p=0.007 and p=0.002, respectively). Higher thrombus density was correlated with worse preprocedural TIMI flow (p<0.001). Patients with higher aspirated volume and surface developed less ST-resolution (p=0.042 and p=0.023, respectively). Conclusions Angiographic outcomes linked with worse prognosis were more frequent among patients with larger extracted thrombus. Despite retrieving larger thrombus load in these patients, current thrombectomy devices fail to deal with thrombotic material adequately. Further studies of novel thrombus aspiration technologies are warranted to improve patient outcomes.